Occupational Health and Safety (OHS) Issues and OHS Information Sources Utilized by Public University Library Personnel in South – West, Nigeria - Oketunji, Serah Funmilayo (MiddleBelt Journal of Library and Information Science, 2014)
A number of contemporary occupational health and safety (OHS) issues have been known to be confronting library personnel in public universities in the developed world and they have also expressed the need for variety of information sources and packaging to support them in overcoming or combating these problems. Whereas, studies on the relationship between Occupational Health and Safety (OHS) information needs, sources and utilization in public university libraries in South-West, Nigeria have probably received inadequate empirical attention. It is in the light of this that the present study investigated occupational health and safety issues, information sources and utilization in public universities in South-West, Nigeria The study adopted descriptive survey research design of the ex-post-facto type. Considering the size of the population total enumeration method was used thereby covering the entire professional and Para-professional library personnel’s in each of the thirteen (13) public university libraries studied giving a total of three hundred and forty- three (343) respondents. Out of 343 questionnaires sent out, 281 were successfully completed and returned and this represents 82%. The questionnaire was validated. Crombact Alpha reliability coefficient obtained was 0.875. Findings revealed that OHS information sources and utilization significantly impact job performance among personnel in public university libraries in South-West Nigeria with the values (R=0.83, P<0.05). The effect of occupational health and safety information utilization on job performance was significant (R = 0.260, P< 0.05) and similarly the effect of OHS availability and utilization on job performance was significant (R =.268, P<0.05)